VALIDATION OF THE REDUCED SPANISH VERSION OF THE MEMORY FUNCTIONING QUESTIONNAIRE (MFQ) IN A SAMPLE OF ELDER PEOPLE OVER 55 YEARS OLD - Alarcón Rubio, David; Fernandez Portero, Cristina (Anales de Psicología / Annals of Psychology, 2008)
In this study we try to analyze the use of the reduced Spanish version of the Memory Functioning Questionnaire as a valued and reliable instrument in a sample (n = 147) of elder people over 55 years old without any evidence of degeneration. The data was obtained of a longitudinal study in the beginning and end of an academic course of the Third Age University Program “Aula de la Experiencia” (Seville University). The factorial analysis of main components with Varimax rotation showed a structure of four factors corresponding to each one of the four original subtest of the questionnaire. The reliability analysis, calculated by the repeated measures pretest-postest with 9 months between measures, indicated a high correlation for each subtest. Also, a high internal consistency was observed for each subtest, calculated by the alpha of Cronbach, which confirms the reliability of the questionnaire. In addition, it was verified that the scores in the questionnaire significantly were not influenced by the demographic characteristics of the participants. In conclusion, the questionnaire can be used like a useful tool to evaluate the operation of the memory in elder populations over 55 years old.